Brand Experience and Engagement: Influences on Brand Loyalty among University Students and Alumni in an Indonesian Higher Education Institution - Jiko Yanandra; Lindiawati Lindiawati (Yayasan Riset dan Pengembangan Intelektual, 2023)
The loyalty of students and alumni to higher education institutions is one of the factors that influences the marketing and sustainability of higher education institutions. Students and alumni often attribute their experience with a college to their level of loyalty. The experience of students and alumni represented by brand experience, the relationship represented by brand engagement and their loyalty to the higher education institution representaed by brand loyalty. This are a factors that strongly influence the sustainability of the higher education institution. The aim of this research at analyzing the influence of brand experience to brand loyalty of the students of Hei’s mediated by brand engagement. This research is quantitative research using primary data obtained through questionnaires filled by 412 students and alumni Hayam Wuruk Perbanas University. This research uses the probability sampling method. Validity and reliability tests were carried out to test the instrument before being distributed to the respondents. The data was analysed using Structural Equation Model (SEM) by WarpPLS. The research results there is a positive relationship between brand experience and brand loyalty, and brand engagement can mediate this relationship. Positive brand experience can lead to a higher level of brand engagement, which in turn can increase brand loyalty among students and alumni of Hayam Wuruk Perbanas University. creating positive brand experiences and growing brand engagement can help universities build and increase a strong student and alumni loyalty.